2019
DOI: 10.1186/s12864-019-6060-z
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Bacillus anthracis strains from Western Siberia reveals a new genetic cluster in the global population of the species

Abstract: Background Anthrax is a zoonotic disease caused by the gram-positive bacterium Bacillus anthracis . The most anthrax-endemic regions of Russia are Siberia and North Caucasus. Previously, genotyping of Russian B.anthracis isolates was carried out using canSNP and MLVA data; these methods yield lower resolution results compared to whole genome SNP analysis (wgSNP). In this research, we have used wgSNP method for genotyping of 10 B.a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Moreover, we would like to focus on lineage B strains. Previously it was shown that B. anthracis strains of the B.Br.001/002 group circulating in Siberia form a separate phylogenetic cluster, named «Siberia» [38]. However, in our work two Siberian B.Br.001/002 strains were combined into one GT5 with the B.Br.CNEVA group, but not with other B.Br.001/002 strains, including not with the strain I-364 isolated in Siberia.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, we would like to focus on lineage B strains. Previously it was shown that B. anthracis strains of the B.Br.001/002 group circulating in Siberia form a separate phylogenetic cluster, named «Siberia» [38]. However, in our work two Siberian B.Br.001/002 strains were combined into one GT5 with the B.Br.CNEVA group, but not with other B.Br.001/002 strains, including not with the strain I-364 isolated in Siberia.…”
Section: Discussionmentioning
confidence: 70%
“…According to our data, the subclade B.Br.002 contains, along with the isolate from Korea, strains isolated in Western Siberia (a separate cluster "Siberia") and Finland [13], although in an earlier work the strain from Finland was described as constituting a separate clade line B.Br.002 with the nearest strains HYU01 from South Korea and BF1 from Germany [14]. Based on the data described, it can be assumed that clade C, the oldest, with a minimum number of isolates, has become a blind branch of the evolution, which has not received further distribution outside the United States.…”
Section: Discussionmentioning
confidence: 88%
“…qPCR results have shown that the obtained isolate is a possible avirulent B. anthracis variant, but we still need to do further studies on the one isolate to be sure about. Isolation of pathogenic STI isolates in Caucasus, Yakutia and Western Siberia were reported by Pisarenko et al (2019). Moreover, both pXO1 and pXO2 plasmids may be lost long storage within ground waters and also under certain other environmental or laboratory conditions (Turnbull et al, 1992;Marston et al, 2005).…”
Section: Discussionmentioning
confidence: 98%